2014
DOI: 10.1515/htmp-2014-0043
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Wettability of Aluminum Based Silicon Carbide Reinforced Particulate Metal Matrix Composite

Abstract: Lately, materials research has shifted to composite materials from monolithic, adjusting to the global need for light weight, low cost, quality, and high performance in structural materials. Every effort aims to develop a material which can be appropriate for various industry and machinery purpose. In the present study, a modest attempt has been made to develop cast aluminum based silicon carbide (SiC) particulate metal matrix composite (MMC) and worked upon to raise the wettability factor between the matrix a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 9 publications
1
25
0
Order By: Relevance
“…An improvement of 47.3% in ultimate tensile strength (UTS), 50% in hardness and 60% in impact strength over the metal alloy were reported. This improvement in mechanical properties can be attributed to the presence of Mg as the principal constituent in AA6063, which acts as a surfactant and augments the wettability between Al and SiC by reducing the oxide layer on the surface of SiC [11]. Tribological properties of AA6063/clay composites have been explored by Agbeleye et al [12] for brake disc rotor applications.…”
Section: Introductionmentioning
confidence: 99%
“…An improvement of 47.3% in ultimate tensile strength (UTS), 50% in hardness and 60% in impact strength over the metal alloy were reported. This improvement in mechanical properties can be attributed to the presence of Mg as the principal constituent in AA6063, which acts as a surfactant and augments the wettability between Al and SiC by reducing the oxide layer on the surface of SiC [11]. Tribological properties of AA6063/clay composites have been explored by Agbeleye et al [12] for brake disc rotor applications.…”
Section: Introductionmentioning
confidence: 99%
“…Recent research has shown that energy efficient microwaves is a newly explored method and it has been applied successfully in processing of various materials, fabricating materials with improved mechanical properties. Microwave sintering is a distinguishing and alternative technique when compared with the existing processes utilizing orthodox heating sources [ 19 , 20 ] with a strong potential of enhanced turn-over and reduced energy consumption.…”
Section: Introductionmentioning
confidence: 99%
“…The measured stress-strain curve of all samples (blocky, mixed, plate) and also that of the pure Al [11] are shown in Fig. 5.…”
Section: Tensile Propertiesmentioning
confidence: 99%
“…Microhardness values of blocky TiAl 3 , plate TiAl 3 , Al and Ti phasesFig. 5Stress-strain curves for three tested FGC samples and pure Al adopted from Singh et al[11] …”
mentioning
confidence: 99%